2002
DOI: 10.1103/physrevb.65.212405
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization and specific heat ofLaTiO3

Abstract: The orbital ground state of LaTiO 3 is still under debate. Recent letters ͓Phys. Rev. Lett. 85, 3950 ͑2000͒; 85, 3946 ͑2000͔͒ discussed a scenario of an orbital liquid, and provided theoretical predictions about orbital contributions to the specific heat. Here we present the results of heat capacity and magnetic measurements. Based on model calculations we determine an electronic ground state which gives g values compatible with the experimentally observed ordered moment and the paramagnetic susceptibility. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
35
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 21 publications
(22 reference statements)
5
35
0
Order By: Relevance
“…The puzzling magnetic properties of LaTiO 3 led Khaliullin and Maekawa to suggest a novel theoretical description for RETiO 3 based on the idea of an orbital liquid. They were able to explain many of the magnetic characteristics of LaTiO 3 [3], but the presumed orbital fluctuations have not been observed [8]. Therefore, magnetism in LaTiO 3 still remains an open issue.…”
mentioning
confidence: 99%
“…The puzzling magnetic properties of LaTiO 3 led Khaliullin and Maekawa to suggest a novel theoretical description for RETiO 3 based on the idea of an orbital liquid. They were able to explain many of the magnetic characteristics of LaTiO 3 [3], but the presumed orbital fluctuations have not been observed [8]. Therefore, magnetism in LaTiO 3 still remains an open issue.…”
mentioning
confidence: 99%
“…In an earlier publication 23 it was mentioned that the anisotropy observed in the paramagnetic regime requires to include the spin-orbit coupling into the crystal-field calculation.…”
mentioning
confidence: 99%
“…13 Furthermore, an orbital contribution to the specific heat, which is predicted by the orbitalliquid model, has not been found in experiment. 14 Hence from the recent experiments it must be concluded that the orbital-liquid model is inappropriate for LaTiO 3 . Moreover, it has been proven, by exact symmetry arguments, that due to a hidden symmetry the superexchange Hamiltonian used in Ref.…”
Section: Introductionmentioning
confidence: 99%